2008
DOI: 10.1515/epoly.2008.8.1.1231
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phthaloylation and succinylation of hemicelluloses by microwave irradiation

Abstract: Rapid phthaloylation and succinylation of wheat straw hemicelluloses with phthaloyl dichloride (PdC) and succinyl chloride (SC) in N,Ndimethylformamide/lithium chloride (DMF/LiCl) system using N-bromosuccinimide (NBS) as a catalyst was achieved for only 5 minutes at 50 °C by microwave irradiation. The degree of substitution (DS) ranged between 0.43 and 1.47. The effect of the molar ratios of xylose units in hemicelluloses to phthaloyl dichloride or succinyl chloride on the degree of substitution was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Referring to previous reports, maleic anhydride-functionalized hemicelluloses exhibited similar thermal stability behavior as the functionalization led to less thermally stable products. 11 A range of wheat straw hemicellulose esters were also observed by Xu et al 50 to have lower thermal stability than the native hemicelluloses and this was also the case for wheat straw hemicellulosic succinates synthesized by Sun et al 37 Xylan succinylates obtained by microwave irradiation 57 were less thermally stable than the native xylan, although this in part could be due to degradation of the polymer as a result of the chosen modification process. Ren et al 51 found that lauroylated hemicelluloses with low DS (<0.78) were less thermally stable than the native biopolymer, while higher DS (>1.56) lead to compounds which were more thermally stable than the starting material.…”
Section: Characterization Of Modified Xylansmentioning
confidence: 72%
“…Referring to previous reports, maleic anhydride-functionalized hemicelluloses exhibited similar thermal stability behavior as the functionalization led to less thermally stable products. 11 A range of wheat straw hemicellulose esters were also observed by Xu et al 50 to have lower thermal stability than the native hemicelluloses and this was also the case for wheat straw hemicellulosic succinates synthesized by Sun et al 37 Xylan succinylates obtained by microwave irradiation 57 were less thermally stable than the native xylan, although this in part could be due to degradation of the polymer as a result of the chosen modification process. Ren et al 51 found that lauroylated hemicelluloses with low DS (<0.78) were less thermally stable than the native biopolymer, while higher DS (>1.56) lead to compounds which were more thermally stable than the starting material.…”
Section: Characterization Of Modified Xylansmentioning
confidence: 72%
“…Further rise of temperature to 80 °C led to a slight fall in DS Q from 0.62 to 0.57, which may be attributed to the degradation of carboxymethyl xylan-type hemicelluloses and more side reactions during the quaternization. 23 The influence of DS C on the DS Q (samples 19−24) was also investigated. DS Q decreased from 0.62 to 0.45 as the DS C increased from 0.49 to 0.84, and thereafter it showed little difference as the DS C was higher than 0.84.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An increase in the reaction temperature from 40 to 70 °C resulted in DS Q increasing from 0.37 to 0.62 due to diffusion and compatibility of the reaction ingredients and the mobility of the reactant molecules. Further rise of temperature to 80 °C led to a slight fall in DS Q from 0.62 to 0.57, which may be attributed to the degradation of carboxymethyl xylan-type hemicelluloses and more side reactions during the quaternization …”
Section: Resultsmentioning
confidence: 99%
“…The increase in DS could be explained by the fact that a higher reaction temperature favors the diffusion and compatibility of the reaction ingredients, the hemicelluloses' ability to swell, and the mobility of the reactant molecules. However, the higher temperature may result in the degradation of hemicelluloses and more side reactions during the carboxymethylation of hemicelluloses , , thus decreasing the DS.…”
Section: Resultsmentioning
confidence: 99%